A4_3 One, Two, Tree. Timber! - Thomas, Kaia; Paton, Charlotte; Wing, Matthew; McCabe, Nat (Physics Special Topics, 2021)
In the popular game Animal Crossing: New Horizons, the character is able to chop down any tree with just three hits. In this paper, we focus on the coconut palm tree, and calculate the force required to do this. We use the flexural strength relation, and found that if the tree was struck at a height of 1m, each hit would have to equate to approximately 395418N in order to chop down the tree. In order to achieve such a force, the impact velocity of the axe on the tree trunk would have to be around 510m/s.